Analisis Penerapan Akuntansi Wakaf Berdasarkan PSAK 112 pada BAZNAS Sumatera Utara - Utami, Dita Sri; Nasution, Yenni Samri Julianti (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the implementation of waqf accounting based on Statement of Financial Accounting Standards (PSAK) 112 at the National Amil Zakat Agency (BAZNAS) of North Sumatra Province. PSAK 112 specifically regulates the recognition, measurement, presentation, and disclosure of waqf transactions, including cash waqf as well as movable and immovable assets. The research method employed is a qualitative approach using interviews, documentation, and literature studies as data collection techniques. The findings reveal that BAZNAS North Sumatra has conducted accounting records and reporting related to waqf, but the implementation has not yet fully complied with PSAK 112. Several aspects, such as the disclosure of separate waqf financial statements, the presentation of waqf assets, and the recognition of economic benefits from waqf management, still require improvements to align with applicable sharia accounting standards. This study contributes by providing empirical evidence regarding waqf accounting practices in zakat management institutions and serves as input for BAZNAS to enhance transparency and accountability in waqf management in the future.